Green Economy and Carbon Investment: Business Strategies for Facing the Global Energy Transition - Hamdani Hamdani; Firayani Firayani (PT. Anagata Sembagi Education, 2025)
The global energy transition has reshaped business dynamics and capital markets through the rise of the green economy and carbon investment as the new foundation of corporate competitiveness. This study analyzes how companies in Indonesia formulate green business strategies while optimizing carbon investment to sustain competitive advantage during the global energy shift. A Systematic Literature Review (SLR) following PRISMA guidelines was employed to identify, screen, and synthesize 24 relevant scientific articles published between 2018 and 2025. The findings reveal that corporate sustainability strategies rely not only on low-carbon technological innovation, energy efficiency, and supply-chain transformation but also on the implementation of carbon investment, participation in carbon credit markets, and access to ESG-based financing. The integration of green economy and carbon investment enhances corporate market reputation, reduces regulatory risks, lowers capital costs, and creates new revenue opportunities through carbon asset monetization. This study concludes that the success of Indonesian companies in navigating the global energy transition is determined by their ability to position the green economy and carbon investment as the core of their long-term business strategies.